Surgical Reimplantation for the Correction of Vesicoureteral Reflux following Failed Endoscopic Injection - Boris Chertin; Ksenia Prosolovich; Sagiv Aharon; Ofer Nativ; Sarel Halachmi (Advances in Urology)
Purpose. In recent years, endoscopic injection became the procedure of choice for the correction of vesicoureteral reflux in the majority of the centers. Unfortunately, endoscopic treatment is not always successful and sometimes requires more than one trial to achieve similar results to that of an open reimplantation surgery. Our aim of this study is to evaluate the feasibility and success rate of open ureteral reimplantation following failed endoscopic procedure. Patients and Methods. During 2004–2010, we evaluated 16 patients with persistent vesicoureteral reflux (grades II–IV) following failed endoscopic treatment. All patients underwent open ureteral reimplantation. All patients were followed with an ultrasound 6 weeks following surgery and every 6 months thereafter for an average of 22 months. Voiding cystography was performed at 3 months after surgery. Results. During unilateral open ureteral reimplantation, the implanted deposit from previous procedures was either excised, drained, or incorporated into the neotunnel with the ureter. Vesicoureteral reflux was resolved in all patients with 100% success rate. No new hydronephrosis or signs of obstruction developed in any of the patients. qDMSA renal scan was available in 8 patients showing improvement of function in 5 and stable function in 3, and no new scars were identified. Conclusions. Open ureteral reimplantation is an excellent choice for the correction of failed endoscopic treatment in children with vesicoureteral reflux.